Enhanced recovery after pulmonary surgery - Eustache, Jules; Ferri, Lorenzo E.; Feldman, Liane S.; Lee, Lawrence; Spicer, Jonathan D. (Journal of Thoracic Disease; Vol 10, Supplement 32 (November 20, 2018): Journal of Thoracic Disease (Enhanced Recovery: The Evidence Supporting Best Perioperative Care in Thoracic Surgery), 2018)
The concept of surgical recovery encompasses the entire perioperative phase of the patient, beginning with the preoperative baseline and culminating in the long-term rehabilitation of the patient in the post-operative phase. Enhanced recovery pathways (ERPs) aim to encompass all phase of the patient trajectory, including the preoperative, perioperative, and postoperative management of surgical patients. While significant literature exists on standardizing and optimizing the perioperative phase, standardizing the pre and post-operative phases remains a topic of debate. Furthermore, with regards to pulmonary surgery, the available data on enhanced recovery remains limited, with no consensus on which components to include within the ERP. The difficulty in identifying specific factors to include within a pathway is in part due to the lack of representative metrics of recovery. Secondly, the strength of ERPs usually lies in the agglomeration of multiple components rather than the individual components themselves. This review provides a brief review on current developments in ERPs in pulmonary surgery, emphasizing novel components in the pre and post-operative care of patients. Furthermore, we discuss the limitations of current metrics used to study recovery, and what steps can be taken to direct future studies that aim to enhance patient recovery after pulmonary surgery.